ZNF580 - a brake on Interleukin-6 - Philipp Stenzel; Kaj Nagorsen; Jonathan Bernd; Ulrike Leppert; Andreas Zakrzewicz; Janine Berkholz (BMC, 2018)
Abstract Background Zinc finger protein 580 (ZNF580) was reported to modulate angiogenesis, endothelial homeostasis and blood pressure control. ZNF580 regulated genes include VEGF-A and IL-8. However, it is unknown if ZNF580 could play a role during inflammation. The aim of this study was to find out if ZNF580 affects the expression of IL-6, if it occurs in monocytic cells and responds to inflammatory mediators. Results Overexpression of ZNF580 reduced LPS-induced promotor activity of IL-6. Consistently, overexpression of ZNF580 reduced by half the LPS-induced expression of IL-6. ZNF580 was strongly expressed in the nucleus of MonoMac6, a human monocytic cell line. LPS-stimulated IL-6 secretion increased when ZNF580 was suppressed with siRNA. After stimulation of MonoMac6 with LPS for 24 h, ZNF580 negatively correlated with the amount of secreted IL-6. In response to LPS, ZNF580 was increased within the first 8 h, followed by a marked decrease after 16 h. This decrease coincided with sustained IL-6 production. Conclusion This study demonstrated that ZNF580 inhibits LPS-induced expression of IL-6. ZNF580 was highly expressed in monocytic cells and therefore may contribute to the modulation of its IL-6 production, at least in response to LPS. This suggests cooperation between ZNF580 and NFκB, which could play a role during sepsis.